Enlarging the knowledge on Graomys griseoflavus (Rodentia: Sigmodontinae) in Patagonia: Distribution and environments - Udrizar Sauthier, Daniel Edgardo (2011)
The Leaf-eared mouse Graomys griseoflavus (Waterhouse 1837) is a medium-sized sigmodontine rodent of the tribe Phyllotini (Hershkovitz 1962) that occurs throughout a wide area of the Chaco and Andean-Patagonic domains, from southcentral Bolivia through western Argentina to central and eastern Santa Cruz province (Yepes 1935, Cabrera 1961, Hershkovitz 1962, Dı´az et al. 2006). The first citation for this species in Patagonia corresponds to the type locality (Hershkovitz 1962: p. 453) cited as ‘‘Near mouth of the Rio Negro, province of Rı´o Negro, Southern Argentina’’ by Waterhouse (1837: pp. 28–29) in the original description. Later, Doering (1881) cited some specimens from the provinces of Neuque´n and Rı´o Negro. Despite these early references, the southern geographic distribution of G. griseoflavus (i.e., south of 398S) is poorly known, basically restricted to a few records based mainly on owl pellets analyses (Nabte 2003, Pardin˜as et al. 2003, 2004, Nabte et al. 2006) and collected specimens (e.g., Daciuk 1974, Monjeau et al. 1997, 1998, Rodrı´guez and Theiler 2007). The Leaf-eared mouse prefers shrubby or wooded areas in arid to semi-arid environments; it is also found in relatively open shrubby steppes with sandy soils and even in naked rocky outcrops (Hershkovitz 1962, Rosi 1983, Corbala´n 2004, Teta et al. 2009). In Patagonia it was frequently caught among shrubs of Larrea divaricata and Prosopis sp. (Udrizar Sauthier 2009).